2021
DOI: 10.1093/humrep/deab130.436
|View full text |Cite
|
Sign up to set email alerts
|

P–437 The ovaries of transgender men indicate effects of high dose testosterone on the primordial and early growing follicle pool

Abstract: Study question Does high-dose testosterone therapy affect the stage distribution, morphological health and DNA damage repair capacity of human ovarian follicles and their survival in vitro? Summary answer Testosterone exposure is associated with reduced follicle growth activation, reduced follicle health and increased DNA damage: these further deteriorate after six days of culture. What is known already: Androgens have divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For individuals AFAB, in vitro studies have shown the teratogenicity of testosterone on fetal anatomic development, though the thresholds are not well defined and the washout period for teratogenicity is unknown 17,22,23. Therefore, all current data suggest that retrieval of oocytes should occur before initiation of GAHT or during a period of cessation from testosterone therapy 7,15.…”
Section: Fertility Preservation Genetic Parenthood and Gestational Pa...mentioning
confidence: 96%
“…For individuals AFAB, in vitro studies have shown the teratogenicity of testosterone on fetal anatomic development, though the thresholds are not well defined and the washout period for teratogenicity is unknown 17,22,23. Therefore, all current data suggest that retrieval of oocytes should occur before initiation of GAHT or during a period of cessation from testosterone therapy 7,15.…”
Section: Fertility Preservation Genetic Parenthood and Gestational Pa...mentioning
confidence: 96%